Problems of Education and Education of Children with Special Educational Needs in Inclusive Education (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the goals and tasks of the inclusive education system and opinions on their solution, the problems of inclusive education and its principles, the implementation of the inclusive education system on a global scale, and many problems and Information about the existence of disabilities, guaranteeing the equal right of students in education, mental problems of children with special educational needs is covered.